ETIKA RELASI KERJA PERSPEKTIF HADIS DAN IMPLIKASINYA BAGI PENCEGAHAN SENIORITAS - Amin, Patuwina; Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the ethics of work relations from the perspective of hadith and its implications for the prevention of negative seniority practices in the work environment. Seniority that originally functioned as a form of appreciation for experience often shifted into a practice of domination, discrimination, and abuse of authority. This research uses a qualitative approach with the type of literature study and thematic hadith method (maudhu'i). The primary data source comes from the hadiths in Saheeh Bukhari and Saheeh Muslim, while secondary data is obtained from relevant books, scientific journals, and previous research. The results of the study show that the hadith contains important ethical values of work relations, such as justice ('adl), responsibility (amanah), humility (tawadhu'), and brotherhood (ukhuwah). These values reject all forms of tyranny, arrogance, and degradation of human dignity. The implications of this study show that the application of hadith values can be the basis for the formation of a fair, inclusive, and humanist work culture, as well as a strategy to prevent harmful seniority practices.